2017
DOI: 10.1155/2017/3832072
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Testing Techniques for the Measurement of Shrinkage and Structural Changes of Fine-Grained Cement-Based Composites during Ageing

Abstract: The paper deals with an experimental analysis focusing on the utilization of a specific measurement technique for determining the development of shrinkage and for monitoring structural changes in fine-grained cement-based composites during their ageing. Advanced measurement equipment and procedure allowing simultaneous measurement of length changes, mass losses, acoustic responses, and temperature development were designed and verified by the experimental investigation. The main scope of the experiments perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…is phenomenon was also noticed in previous research [20,22,23]. Zhang et al [23] reported a maximum swelling strain of 70 μm/m and 250 μm/m for C30 and C80 concrete, respectively.…”
Section: Early-age Shrinkagesupporting
confidence: 78%
See 1 more Smart Citation
“…is phenomenon was also noticed in previous research [20,22,23]. Zhang et al [23] reported a maximum swelling strain of 70 μm/m and 250 μm/m for C30 and C80 concrete, respectively.…”
Section: Early-age Shrinkagesupporting
confidence: 78%
“…Comparing the four figures, it could be noted that the shrinkage rate in Phase I increased with the increase of temperature and decreased with the increase of relative humidity because higher temperature and lower relative humidity resulted in a higher water evaporation rate. Shrinkage in the first phase was mainly caused by bleeding and settlement of plastic shrinkage [20,21]. e increased shrinkage rate of samples with and without CPF liner was identical under certain environment conditions because the samples under the same temperature, relative humidity, and wind speed had the same water evaporation rate.…”
Section: Early-age Shrinkagementioning
confidence: 98%
“…The phenomenon of swelling is clearly visible from the measurements in the first 24 hours of ageing when the hydration heat is generated at the highest rate (approx. 200 J/g per 24 h) [31,33]. The particular contribution of all the above-mentioned phenomena is the object of ongoing experimental measurement.…”
Section: Resultsmentioning
confidence: 99%
“…The design of the weighing table as well as the details of the measurement procedure are protected by industrial property rights held by Brno University of Technology registered in the national patent database under application number 2013-961 [30]. For details about measurement techniques see [31].…”
Section: Test Equipment Andmentioning
confidence: 99%
“…The compressive strength of specimens [28] at 28 days is shown in Figure 5, and the flexural strength of specimens at 28 days is shown in Figure 6.…”
Section: Mechanical Strengthmentioning
confidence: 99%